The Use of Language in Advertisement in Core Area of Khandbari - Guragai, Dandapani (BARUN Journal, 2024)
The research entitled ‘The Use of Language in Advertisements in the Core Area of Khandbari’ was conducted to analyse the use of language of advertisements in terms of vocabularies, script, creativity and forms of language use. It was based on the survey under quantitative research design. Fifty images of advertisements were collected from the main bazaar of Khandbari municipality. These images were selected as samples for the study using non-random purposive sampling procedure. As per the objectives of the research, a checklist was used to analyse the choice of vocabularies and use of language in the advertisements. Simple statistical tools such as frequency and percentile were used to analyse and interpret the data. The study found out that two languages, Nepali and English, were used in the advertisements. Nepali was given high priority. The majority of the advertisements were monolingual. Transliteration was found in thirty-one samples out of 50. Devanagari script was used in twenty-nine samples. Code mixing was used in fourteen samples (28%). The research consists of four chapters. The first chapter consists of background of the study, objectives of the study, significance, delimitation of the study and review of related literature. The second chapter deals with research design, method, sample and sampling procedures, research tools, sources of data, data collection procedures and ethical consideration. Similarly, third chapter deals with interpretation of results and discussion of findings. Finally, the fourth chapter presents conclusions followed by policy related, practice related and further research related implications of the study.